Self-rated health, subjective social status in school and socioeconomic status in adolescents: a cross-sectional study - Junia Joffer; Renée Flacking; Erik Bergström; Eva Randell; Lars Jerdén (BMC, 2019)
Abstract Background Social position, traditionally measured by objective data on socioeconomic status (SES), is linked to health status in adults. In adolescents, the association is more uncertain and there are some studies suggesting that subjective social status (SSS) might be more adequate in relation to health. This study aimed to examine associations between SSS in school, SES and self-rated health (SRH) in adolescent boys and girls. Methods A descriptive cross-sectional research design with quantitative survey data was used. The study involved 705 Swedish adolescents in upper secondary school (17-18-year-olds). SRH was measured with a single-item question and SSS by a question where adolescents were asked to assess their social position within their school. Formal education level of the parents was used as a proxy for objective SES. Univariable and multivariable ordinal regression analyses were conducted to assess the associations between SRH and SSS in school and SES. Results In the multivariable analysis, SSS in school was positively associated with SRH, whereas no significant association between SES and SRH was found. The proportion of adolescents with high SRH increased with higher steps on the SSS ladder. Significant gender differences were found in that boys rated their SRH and SSS in school higher than girls did. Conclusions The study shows that self-rated health in adolescents is related to perceived social position in school. Subjective social status in school seems to be a useful health-related measure of social position in adolescents.